2010
DOI: 10.1101/gad.1882810
|View full text |Cite
|
Sign up to set email alerts
|

Proper regulation of a sperm-specific cis-nat-siRNA is essential for double fertilization in Arabidopsis

Abstract: Natural cis-antisense siRNAs (cis-nat-siRNAs) are a recently characterized class of small regulatory RNAs that are widespread in eukaryotes. Despite their abundance, the importance of their regulatory activity is largely unknown. The only functional role for eukaryotic cis-nat-siRNAs that has been described to date is in environmental stress responses in plants. Here we demonstrate that cis-nat-siRNA-based regulation plays key roles in Arabidopsis reproductive function, as it facilitates gametophyte formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
187
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(195 citation statements)
references
References 57 publications
5
187
0
3
Order By: Relevance
“…The kpl-1, tt16-2, tt16-3, ProFIS:FIS-GUS, and ProMEA:MEA-GUS lines are in the Ws-2 accession (Luo et al, 2000;Nesi et al, 2002;Ron et al, 2010). The agl62-2/+, mc1, lsd1, fie-12/+, msi1-1/+, fis2-5/+, goa-1, and ProFWA:FWA-GUS lines are in the Col-0 accession (Kinoshita et al, 2004;Coll et al, 2010;Prasad et al, 2010;Roszak and Köhler, 2011).…”
Section: Plant and Genetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kpl-1, tt16-2, tt16-3, ProFIS:FIS-GUS, and ProMEA:MEA-GUS lines are in the Ws-2 accession (Luo et al, 2000;Nesi et al, 2002;Ron et al, 2010). The agl62-2/+, mc1, lsd1, fie-12/+, msi1-1/+, fis2-5/+, goa-1, and ProFWA:FWA-GUS lines are in the Col-0 accession (Kinoshita et al, 2004;Coll et al, 2010;Prasad et al, 2010;Roszak and Köhler, 2011).…”
Section: Plant and Genetic Materialsmentioning
confidence: 99%
“…To investigate the role of each of the two fertilization events independently, we examined nucellus degeneration in the Arabidopsis kokopelli (kpl) mutant (Ron et al, 2010). kpl plants display random single-fertilization events that result in seeds carrying either the endosperm or the embryo.…”
Section: Fertilization Of the Central Cell Generates A Signal That Trmentioning
confidence: 99%
“…In the RdDM pathway, both PolV-dependent nascent scaffold transcripts and hc-siRNAs are essential to guide de novo cytosine DNA methylation, which maintains the silencing of repeats (Wierzbicki et al, 2008;Wierzbicki et al, 2009). Nat-siRNAs are products of processed natural antisense transcripts and have been shown to be involved in plant stress resistance and reproduction (Borsani et al, 2005;Katiyar-Agarwal et al, 2006;Ron et al, 2010). ta-siRNAs are initiated by DCL1-dependent miRNA-guided cleavage of noncoding transcripts, which are then stabilized by SUPPRESSOR OF GENE SILENCING3 (SGS3) and converted to double-stranded RNA (dsRNA) by the actions of RDR6 (Peragine et al, 2004;Vazquez et al, 2004;Xie et al, 2004;Allen et al, 2005;Yoshikawa et al, 2005;Axtell et al, 2006).…”
mentioning
confidence: 99%
“…The nat-siRNA biogenesis is dependent on DCL1, DCL2, and RDR6 (Borsani et al, 2005;Ron et al, 2010). Zhang et al (2012) also found that some nat-siRNAs were dependent on DCL1, DCL3, and RDR2.…”
Section: Mapping Srnas To Cis-natsmentioning
confidence: 97%